Effects of gloss type, gloss position, and working memory capacity on second language comprehension in electronic reading. Issue 7 (3rd September 2021) - Varol, Burcu; Erçetin, Gülcan
Abstract: This study explores the role of glosses and working memory capacity (WM) in second language (L2) learners' recall and comprehension in electronic reading. Glosses were investigated in terms of the type of information they provided (lexical versus topic-level) and their location on the screen (pop-up window versus separate window). One hundred-twenty highly proficient participants were classified into high- and low-WM groups and were assigned to one of the four treatment conditions, namely pop-up window topic-level glosses, separate window topic-level glosses, pop-up window lexical glosses, separate window lexical glosses. The participants were asked to read an electronic text while a built-in tracking software recorded their interactions. After reading, the participants were given a free recall task and a multiple choice comprehension test. Findings showed that the effects of gloss content depended on the type of task used to gauge comprehension while the effect of gloss location was less clear-cut. Additionally, WM capacity played a major role in comprehension. Probing into the participants' use of annotations revealed that lexical glosses led to longer reading times and pop-up conditions triggered more frequent look-up behavior.